Update on chromosomal locations for psychiatric disorders: report of the interim meeting of chromosome workshop chairpersons from the VIIth World Congress of Psychiatric Genetics, Monterey, California, October 14-18, 1999. - DeLisi, L; Craddock, N; Detera-Wadleigh, S; Foroud, T; Gejman, P; Kennedy, J; Lendon, C; Macciardi, F; McKeon, P; Mynett-Johnson, L; Nurnberger, J; Paterson, A; et al. (2000)
The Chromosome Workshops at the annual World Congress of Psychiatric Genetics have proven to be useful tools to compare data and to assess the significance of results from independent studies. These sessions have also been able to integrate the findings across diagnostic groups. These workshops will continue to extend the previously reported information to include new data sets at future meetings. The integrative maps and consensus reports will be available in regular publications and on the World-Wide WEB. No gene has yet been isolated for the major psychiatric disorders-schizophrenia, bipolar disorder, alcoholism, or autism. The use of linkage strategies alone to localize genes for these complex disorders remains to be established and alternative approaches should continue to be explored.